1992
DOI: 10.1002/hlca.19920750206
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides. Part XXXVIII.. Syntheses and characterization of phosphorothioate analogues of (2′–5′) adenylate dimer and trimer and their 5′‐O‐monophosphates

Abstract: Dedicated to Prof. Dr. Wilhelm Fleischhacker on the occasion of his 60th birthday (8.X1.91) ~ ~~The chemical syntheses of the phosphorothioate of (2'-5')adenylate dimer (see 6a, 6b) and trimer (see 1 la, 1 lb, 12a, 12b) as well as of their 5'-monophosphates (see 15a, 15b, 16a, 16b) using the phosphoramidite method are described. The resulting diastereoisomer mixtures were separated into the pure components by chromatographical means. All synthetic intermediates were characterized by TLC, elemental analysis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Modifications to the backbone and 5'-mono-/triphosphate moiety: Mannose phosphate adduct Human_pp5'A2'p5'A2'p5'A P,y-Methylenephosphonate pCHzppA2'p5'A2'p5'A Linkage isomers A2'p5'A3'p5'A A3'p5'A2'p5'A (pp)p5'A3'p5'A3'p5'A (pp)p5'A2'~5'A3'~5'A (pp)p5'A3'p5'A2'p5'A P3-n-decylaminotriphosphate analogue n-decyl-NH-ppp5'A2'p5'A2'p5'A Methylthiophosphate analogue H,CSp5'A2'p5'A2'p5'A2'ppOCH, Phosphorodithioate analogue p5'A2'(~2p)5'A2'(~2p)5'A Phosphorothioate analogues (Rp)-P_thioadenylyl(2'-5')adenosine (Sp)-P-thioadenylyl(2'-5')adenosine (Rp)-P-thioadenylyl(2'-5')-(Rp)-P-thioadenylyl(2'~5')adenosine~ (Rp)-P-thioadenylyl(2'-5')-(Sp)-P-thioadenylyl(2'-5')adenosine' (Sp)-P-thioadenylyl(2'-5')-(Rp)-P-thioadenylyl(2'-5')adenosine~ (Sp)-P-thioadenylyl(2'-5')-(Sp)-P-thioadenylyl(2'-5')adenosine~ also diasteromeric tetramers Adenylyl(2'-5')-(Rp)-P_thioadenylyl(2'-5')adenosine Adenylyl(2'-5')-(Sp)-P-thioadenyly1(2'-5')adenosine (Rp)-P-thio-3'-deoxyadenylyl(2'-5')-(Rp)-P-thio-3'-deoxyadenylyl(2'-5')-3'~ deoxyadenosine Bisbal et al, 1987Bayard et al, 1986Imai and Torrence, 1984Drocourt et al, 1982Bayard et al, 1985Sawai et al, 1983Nyilas et al, 1986Kovacs et al, 1993, 1995Kwiatkowski et al, 1981Kwiatkowski et al, 1982Sawai et al, 1985bPfleiderer et al, 1994Visser et al, 1986Lesiak er al., 1989den Hartog et al, 1981Charubala and Pfleiderer, 1980aKariko and Ludwig, 1985Watling et al, 1985Beigelman et al, 1995Charubala and Pfleiderer, 1992Charubala and Pfleiderer, 1988Charubala and Pfleiderer, 1992 also Battistini et al, 1992also Shimazu et al, 1992also Nelson et al, 1984Charubala et al, 1991De Vroom et al, 1987Sobol et al, 1993a…”
Section: Mmt P-monomethoxytritylmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifications to the backbone and 5'-mono-/triphosphate moiety: Mannose phosphate adduct Human_pp5'A2'p5'A2'p5'A P,y-Methylenephosphonate pCHzppA2'p5'A2'p5'A Linkage isomers A2'p5'A3'p5'A A3'p5'A2'p5'A (pp)p5'A3'p5'A3'p5'A (pp)p5'A2'~5'A3'~5'A (pp)p5'A3'p5'A2'p5'A P3-n-decylaminotriphosphate analogue n-decyl-NH-ppp5'A2'p5'A2'p5'A Methylthiophosphate analogue H,CSp5'A2'p5'A2'p5'A2'ppOCH, Phosphorodithioate analogue p5'A2'(~2p)5'A2'(~2p)5'A Phosphorothioate analogues (Rp)-P_thioadenylyl(2'-5')adenosine (Sp)-P-thioadenylyl(2'-5')adenosine (Rp)-P-thioadenylyl(2'-5')-(Rp)-P-thioadenylyl(2'~5')adenosine~ (Rp)-P-thioadenylyl(2'-5')-(Sp)-P-thioadenylyl(2'-5')adenosine' (Sp)-P-thioadenylyl(2'-5')-(Rp)-P-thioadenylyl(2'-5')adenosine~ (Sp)-P-thioadenylyl(2'-5')-(Sp)-P-thioadenylyl(2'-5')adenosine~ also diasteromeric tetramers Adenylyl(2'-5')-(Rp)-P_thioadenylyl(2'-5')adenosine Adenylyl(2'-5')-(Sp)-P-thioadenyly1(2'-5')adenosine (Rp)-P-thio-3'-deoxyadenylyl(2'-5')-(Rp)-P-thio-3'-deoxyadenylyl(2'-5')-3'~ deoxyadenosine Bisbal et al, 1987Bayard et al, 1986Imai and Torrence, 1984Drocourt et al, 1982Bayard et al, 1985Sawai et al, 1983Nyilas et al, 1986Kovacs et al, 1993, 1995Kwiatkowski et al, 1981Kwiatkowski et al, 1982Sawai et al, 1985bPfleiderer et al, 1994Visser et al, 1986Lesiak er al., 1989den Hartog et al, 1981Charubala and Pfleiderer, 1980aKariko and Ludwig, 1985Watling et al, 1985Beigelman et al, 1995Charubala and Pfleiderer, 1992Charubala and Pfleiderer, 1988Charubala and Pfleiderer, 1992 also Battistini et al, 1992also Shimazu et al, 1992also Nelson et al, 1984Charubala et al, 1991De Vroom et al, 1987Sobol et al, 1993a…”
Section: Mmt P-monomethoxytritylmentioning
confidence: 99%
“…Therefore, the 3'-hydroxyl of the second (from the 3'-terminus) nucleotide residue of 2-5A is critical for binding to RNase L. Baglioni et al (1981a) . None of these compounds bind to or activate RNase L. The phosphorothioate analogues of 2-5A dimer and trimer cores, as well as their 5'-monophosphates, were prepared by the phosphoramidite method, and the diasteromers were separated by chromatographic means and fully characterized by physical means (Charubala and Pfleiderer, 1992).…”
Section: Cleawage Specificitymentioning
confidence: 99%
“…To be applicable as a drug, the 2‐5A must exhibit a good cellular uptake and resistance against biodegradation. Numerous modified 2‐5A pro‐nucleotides, such as phosphorothioate, alanyltyrosine, 2′‐ O ‐phosphoglyceryl, 5′‐capped, aminofuctionalized and phosphoramidate derivatives as well as 3′‐deoxyadenosine, 3′‐ O ,4‐C‐bridged adenosine, 3′‐fluoro‐3‐deoxyadenosine, 3′‐ O ‐methyladenosine and 3′‐amino‐3′‐deoxyadenosine analogues have been synthesized to increase the stability in serum and cytoplasm. Several techniques have also been tested to enhance the cell delivery of 2‐5A and their modified analogues, as an example, encapsulation in liposomes and conjugation to lipophilic groups, but no satisfactory prodrug strategy for the enhancement of cellular uptake has been developed.…”
Section: Introductionmentioning
confidence: 99%
“…10 -14 The phosphorothioate linkage has a chiral center at the phosphorous atom, which regulates the stereochemical course of the enzymatic process [15][16][17] such as binding to and activation of RNase L. 11,14 Enzymatically, 2Ј,5Ј phosphorothioate oligoadenylates with the Rp configuration are produced from Sp-ATP␣S by 2-5A synthetase. 12,13 2Ј,5Ј Phosphorothioate triadenylates with all possible thiophosphoryl configurations have been chemically prepared, 18 and their biological activities have been evaluated. 11,14 Lesiak et al demonstrated that 5Ј-thiophosphoryl 2-5A dramatically enhanced resistance to degradation by phosphatase and has strong biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The structure of the resulting phosphorothioate oligoadenylates was identified by selective enzyme digestion, an ESI-mass spectrum, and a comparison of the 31 P-NMR and HPLC retention time on a reversephase column. 18,21 The polymerization reaction of Imp(S)A took place with high regio-and stereoselectivity, although no protecting group was used. 5Ј-Thiophosphoryl 2Ј,5Ј phosphorothioate oligoadenylates with the Rp configuration from diadenylate to tetraadenylate were obtained in substantial yields, along with small amounts of the corresponding diadenylate and triadenylate with the Sp-phosphorothioate configuration.…”
Section: Introductionmentioning
confidence: 99%